Remote controlled optical manipulation of bimetallic nanoparticle catalysts using peptides. Issue 7 (18th March 2021) - Lawrence, Randy L.; Olagunju, Mary O.; Liu, Yang; Mahalingam, Krishnamurthy; Slocik, Joseph M.; Naik, Rajesh R.; Frenkel, Anatoly I.; Knecht, Marc R.
Abstract : Remote optical manipulation of peptide ligands on bimetallic nanoparticle surfaces allows for tunable catalytic reactivity. Abstract : Bimetallic nanoparticles remain a promising avenue to achieve highly reactive catalysts. In this contribution, we demonstrate the use of a photoswitchable peptide for the production of PdAu bimetallic nanoparticles at a variety of Pd : Au ratios. Using this peptide, the biomolecular overlayer structure can be switched between two different conformations ( cis vs. trans ) via light irradiation, thus accessing two different surface structures. The composition and arrangement of the materials was fully characterized, including atomic-level analyses, after which the reactivity of the bimetallic materials was explored using the reduction of 4-nitrophenol as a model system. Using these materials, it was demonstrated that the reactivity was maximized for the particles prepared at a Pd : Au ratio of 1 : 3 and with the peptide in the cis conformation. Such results present routes to a new generation of catalysts that could be remotely activated for on/off reactivity as a function of the ligand overlayer conformation.